معايير اختيار القيادات الإدارية العُليا وعلاقتها بمستوى الأداء الوظيفي دراسة حالة: المؤسسة الوطنية للنفط والشركات التابع لها بنغازي/ ليبيا - مسعود جميلة عبد النبي محمد; البركاوي ابتسام خليفة (Scientific Journal of University of Benghazi, 2022)
The study aims to demonstrate the criteria for choosing top management leaders and their relationship to the level of job performance in oil companies that operate within the Benghazi district. The relationship between the standards used to choose senior management leaders and the level of their performance is assessed as well. The study population consists of all management in the companies' subsidiary to the national oil department in Benghazi. These include 14 companies, of which 10 are completely owned by the national oil department, the remaining 4 being contractual ones. However, due to the difficulty of interviewing all managers in order to obtain the necessary data for the study, only enterprises that operate or are located within Benghazi city were included. This demographic includes board directors, department heads, general managers, and executives from the enterprises under investigation (120 subjects). Many noteworthy results were obtained, leading to recommendations that were of significant contribution to the field of study.